2011
DOI: 10.1016/j.rse.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing chlorophyll a of optically complex waters (rias Baixas, NW Spain): Application of a regionally specific chlorophyll a algorithm for MERIS full resolution data during an upwelling cycle

Abstract: This study takes advantage of a regionally specific algorithm and the characteristics of Medium Resolution Imaging Spectrometer (MERIS) in order to deliver more accurate, detailed chlorophyll a (chla) maps of optically complex coastal waters during an upwelling cycle. MERIS full resolution chla concentrations and in situ data were obtained in three Galician rias (NW Spain) and the adjacent shelf, an area of extensive mussel cultures that experiences frequent harmful algal events. Regionally focused algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 64 publications
1
28
0
1
Order By: Relevance
“…Their results showed that an algorithm based on two band-ratios (Rrs443/Rrs510 and Rrs443/Rrs555) yielded an estimation error of 70% using in situ radiometric measurements and 95% when using SeaWiFS-derived Rrs. Other studies in optically complex coastal waters showed that it is often necessary to avoid band-ratio-based algorithms to better reflect the specificity of the local/regional biophysical characteristics [66][67][68][69][70]. As part of the CoastColor validation program, the accuracy of a neural network approach was applied to MERIS to estimate Chl.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that an algorithm based on two band-ratios (Rrs443/Rrs510 and Rrs443/Rrs555) yielded an estimation error of 70% using in situ radiometric measurements and 95% when using SeaWiFS-derived Rrs. Other studies in optically complex coastal waters showed that it is often necessary to avoid band-ratio-based algorithms to better reflect the specificity of the local/regional biophysical characteristics [66][67][68][69][70]. As part of the CoastColor validation program, the accuracy of a neural network approach was applied to MERIS to estimate Chl.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have moved toward the differentiation of water types in optically complex environments using in situ and/or satellite‐derived reflectance data. Most of these studies have considered the range of optical classes in marine systems (English Channel and North Sea: Lubac and Loisel ; Tilstone et al ; Vantrepotte et al , Iberian coastal waters: Spyrakos et al ; Adriatic Sea: Mélin et al , Yellow Sea: Ye et al ; Northwest Atlantic shelf: Moore et al , global ocean: Moore et al , global coastal waters: Mélin and Vantrepotte ) with only a few studies focussed on inland systems (lakes and reservoirs in China: Le et al ; Shen et al ; Estonian and Finnish lakes: Reinart et al ). Overall, these classification schemes can substantially improve the remote sensing products associated with individual optical water types (OWTs), and have demonstrated the need for a better understanding of the underlying variability especially in nearshore and inland waterbodies (Moore et al ).…”
Section: Symbols and Acronymsmentioning
confidence: 99%
“…Machine-learning algorithms based on simulated datasets have been widely used to address this issue; however, they still fail to provide accurate results in regional and atypical situations (e.g. Spyrakos et al, 2011;Palmer et al, 2015). Moreover, careful selection of the initial inputs and parameterisation of these models are necessary to avoid imprecision in the prediction of the output and over-fitting.…”
Section: Special Issue Science Of the Total Environmentmentioning
confidence: 99%